2016
DOI: 10.1002/2015jb012305
|View full text |Cite
|
Sign up to set email alerts
|

Aeromagnetic investigation of southern Calabria and the Messina Straits (Italy): Tracking seismogenic sources of 1783 and 1908 earthquakes

Abstract: Southern Calabria and the NE corner of Sicily (Italy) were struck in 1783 and 1908 A.D. by two of the most catastrophic earthquakes ever in European history. Although it is generally acknowledged that the seisms were yielded by normal faults rupturing the upper crust of the Calabria‐Peloritani terrane, no consensus exists on seismogenic source location and orientation. Here we report on a high‐resolution low‐altitude aeromagnetic survey of southern Calabria and Messina Straits. In southern Calabria we document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 78 publications
(157 reference statements)
1
17
0
Order By: Relevance
“…Conversely, other studies (e.g., Grauch, ; Hudson et al, ) showed that also faults crosscutting lower magnetization continental sediments can be highlighted by aeromagnetic maps. Recently, Minelli et al () related the aeromagnetic residual anomalies of south Calabria (Italy) to the faults responsible of the catastrophic 1783 and 1908 earthquakes and suggested that magnetic anomalies are generated by an unexposed ophiolitic layer displaced by active normal faults. In all such cases, the magnetic image of active faults seems rather obvious, as they cut strongly magnetic rocks (basic volcanics and ophiolites) or continental sediments, which are known for generating lower but not negligible induced magnetization, in the order of 5 × 10 −3 A/m at midlatitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, other studies (e.g., Grauch, ; Hudson et al, ) showed that also faults crosscutting lower magnetization continental sediments can be highlighted by aeromagnetic maps. Recently, Minelli et al () related the aeromagnetic residual anomalies of south Calabria (Italy) to the faults responsible of the catastrophic 1783 and 1908 earthquakes and suggested that magnetic anomalies are generated by an unexposed ophiolitic layer displaced by active normal faults. In all such cases, the magnetic image of active faults seems rather obvious, as they cut strongly magnetic rocks (basic volcanics and ophiolites) or continental sediments, which are known for generating lower but not negligible induced magnetization, in the order of 5 × 10 −3 A/m at midlatitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Using (a) updated GPS horizontal velocities (Devoti et al, 2017), (b) a detailed 3-D reconstruction of the subduction interface geometry (Maesano et al, 2017), (c) a recent release of the Italian earthquake catalog (Rovida et al, 2016), and (d) upper crustal fault geometries (Database of Individual Seismogenic Sources Working Group, 2015;Minelli et al, 2016), we investigated the short-term behavior of the Calabrian subduction zone and its potential role in explaining the observed, anomalously low strain rates.…”
Section: 1002/2017gl076554mentioning
confidence: 99%
“…The digital elevation model (DEM) is fromRyan et al (2009). (b) NW (fromAloisi et al, 2012;Galli & Bosi, 2002, 2003Galli & Peronace, 2015;Galli & Scionti, 2006;Minelli et al, 2016), SE (from DISS Working Group, 2015;Tiberti et al, 2017) dipping active fault data sets and subduction interface geometry. (c) Three-dimensional view of the broader study area is toward SSE.…”
mentioning
confidence: 99%
“…It has important applications in the fields of geomagnetic navigation background field construction, mineral resources development, seismogenic sources tracking, hidden tectonic and volcanic structures revealment, etc. (Beamish & White, 2011; De Ritis et al., 2010; Goodge & Finn, 2010; Hood, 2007; Liu et al., 2018, 2021; Minelli et al., 2016).…”
Section: Introductionmentioning
confidence: 99%